Adverse Drug Reactions Reporting Profile in Tertiary Referral Hospital: A Retrospective Pharmacovigilance Study in Indonesia - Cinantya Meyta Sari; Budi Suprapti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Pharmacovigilance is administered to several pharmacological classes of drugs worldwide. However, there are still insufficient data regarding the prevalence and general characteristics of drug reactions, especially in developing countries. Objective:  This study aimed to determine the prevalence and characteristics of ADRs, including the pharmacological class involved, and report and classify the clinical manifestations associated with ADRs. Methods: This retrospective study was based on patient ADR reports during observation. Prevalence, patient demographics, and other data were evaluated using descriptive statistics. Results: Of 773 reports that met the inclusion criteria, most were doctors (80.6%), followed by pharmacists (18.7%). Of the total cases, 430 (55.6%) occurred in the women. Most suspected ADRs occurred in the 19-60 years age group (583; 75.4%). The highest incidence of ADR was observed in patients using antineoplastic agents (19.5%), systemic antibacterials (16.4%), or antihypertensives (12.5%). The majority of clinical manifestations were gastrointestinal disorders (41.7%), and approximately 309 (40%) ADR cases continued with antagonists/antidotes. Approximately 62% of the patients who experienced ADRs recovered. Conclusion: Antineoplastic, systemic antibacterial, and antihypertensive drugs appeared to be the most common drugs used for suspected ADR cases in this hospital. ADR reporting has been running well, but not all healthcare workers have participated actively. Hopefully, the results of this research will contribute to the upcoming strategies for pharmacovigilance activities in this hospital and other healthcare facilities to improve the quality and quantity of ADR reporting and increase the safety of medication usage.